Games, Ideas and Activities for Primary Literacy - Glynne, Hazel and Snowden, Amanda (New Dehli Pearson, 2014)
Description 'It really is such a valuable resource for teachers and so full of practical ideas!...I can say with confidence that these ideas will be highly valued by teachers.' - Bob Cox, Director: Searching for Excellence Ltd, Learning Consultant, Advanced Skills Teacher Designed with busy teachers in mind, the Classroom Gems series draws together an extensive ion of practical, tried-and-tested, off-the-shelf ideas, games and activities, guaranteed to transform any lesson or classroom in an instant. Easily navigable, allowing you to choose the right activity quickly and easily, these invaluable resources are guaranteed to save you time and are a must-have tool to plan, prepare and deliver first-rate lessons ?
Include Illustrations
Keywords: Primary Literacy